THE SYRIAN CRISIS: A LOCAL CONFLICT OR A SYSTEMIC WAR? (Вісник: Міжнародні відносини, 2025)
Background. The post-bipolar system of international relations is in a state of deep crisis: global governance institutions are ineffective, the balance of power is disturbed, the number of political, economic and cultural contradictions is only growing, and global problems of humanity are not being solved. The local conflict in Syria has grown into a systemic war, which has significantly transformed the existing international system and determined a number of subsequent events. The article examines in detail the Syrian war from the point of view of its systemic nature and impact on the global balance of power.Methods. The study was based on a combination of two scientific approaches, namely: political realism and a systemic approach. The synthesis of these two concepts makes it possible to analyze the Syrian events from different angles: on the one hand, the role of individual actors in the conflict is highlighted in accordance with their own interests, and on the other hand, the civil war in Syria is considered as a single system of interconnected elements that interact with each other.Results. The article examines in detail the concept of "systemic war" and its impact on the international system, analyzes systemic wars that have taken place in the history of international relations, and proves that the Syrian crisis is also one of the systemic wars that have significantly changed the global balance of power.Conclusions. The Syrian conflict has significantly transformed the existing system of international relations, led to a change in the balance of power and the formation of new alliances, determined further armed conflicts and allowed contenders for leadership (China, Russia) to challenge the leader of the system (the United States).